Artikel MODERASI BERAGAMA SEBAGAI SARANA MEMPERTAHANKAN PREDIKAT SINGKAWANG KOTA TERTOLERAN - Venansius; Kristianus Atok (STP St. Bonaventura Medan, 2025)
This article discusses the importance of religious moderation in maintaining religious harmony in Singkawang. As one of the most tolerant cities in Indonesia, Singkawang has managed to foster an inclusive atmosphere despite its religious diversity. The purpose of this study is to analyze how religious moderation contributes to maintaining religious harmony in Singkawang and its implications for the broader national context. The study uses a qualitative approach with descriptive analysis, focusing on the role of local government, religious leaders, and communities in promoting religious moderation. The results show that the implementation of religious moderation in Singkawang has led to positive outcomes, such as reduced religious intolerance and increased cooperation among religious communities. The study concludes that religious moderation is essential to preserving the city's tolerant status and ensuring harmonious coexistence in a diverse society. The findings suggest that the government, religious leaders, and the public must work together to maintain this harmony by promoting dialogue, mutual respect, and understanding. It is hoped that Singkawang can serve as a national model for religious tolerance in Indonesia.